A Pause in Peripheral Perspectives: Sergei Diaghliev's 1898 Exhibition of Russian and Finnish Art - Ksenia Pavlenko (Slovo, 2017)
A Pause in Peripheral Perspectives: Sergei Diaghliev's 1898 Exhibition of Russian and Finnish Art